Power/Ground Mesh Area Optimization Using Multigrid-Based Technique - Wang, Kai; Marek-Sadowska, Malgorzata (Design, Automation, and Test in Europe: Proceedings of the conference on Design, Automation and Test in Europe - Volume 1; 03-07 Mar. 2003, 2003)
In this paper, we present a novel multigrid-based technique for power/ground mesh area optimization subject to reliability constraints. The multigrid-based technique is applied to reduce a large-scale mesh to a much coarser one. The reduced mesh can be efficiently optimized. The solution for the original mesh is then computed using a back-mapping process. Experimental results are very encouraging. Large-scale power/ground meshes with millions of nodes can be solved in a few minutes. The proposed technique not only speeds up the optimization process significantly without compromising the quality of solutions, but also brings up a possibility of incorporating the power/ground mesh optimization into other physical design stages such as signal routing.